Takhrij and Syarah Hadith of Agrotechnology: Olive Fruit Efficacy Study - Muhammad Ihsan Sanjani; Wahyudin Darmalaksana; adjat Sudrajat (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet. About the properties of olives. This research method is qualitative through the takhrij and sharah hadith approaches with agrotechnological analysis. Results and discussion of this study are the properties of olives which are very beneficial for the body and were highly recommended by the Prophet Muhammad. The conclusion of this study is the hadith and syarah of the Prophet SAW, regarding olives with agrotechnological analysis informing that the content contained in olives is beneficial for the body